Women in Capitalism: Notes for a feminist education (Research, Society and Development, 2021)
This article presents feminism as a practice of liberating education. It rescues the History of women, problematizing the death of thousands of “witches”, in Europe and in the world, in the beginning of modernity and analyzes the role assigned to women by the capitalist system. The study presents the history of the submission of women to the capitalist system and raises the following problem: What contributions does the study of the rise of the capitalist system represent to a feminist education? As a general objective, the idea of ​​presenting the history of the submission of women to the capitalist system was outlined in order to understand what contributions the study of capitalist ascension presents to a feminist education. The following specific objectives were listed: i. Analyze, based on the work “O Calibã e a Bruxa”, the history of the rise of capitalism and the situation of women; ii. engender, from a diverse bibliography, a perspective on the current situation of women in contemporary capitalism; iii. to present the contents related to a feminist education and; iv. reflect on the potential of feminist education at all levels of education. The bibliographic rescue was the methodological trajectory of this research and the way to organize the study was the Immanent Reading (LESSA, 2014). It is pointed out that despite the recognition of the need for a radical transformation of the economic system, it is not necessary that we have a transformation in the mode of production in order for us to begin to untie the knots of the bonds to which we are subjected and feminist education is one of the ways of doing it.